Hubungan Faktor-Faktor Lingkungan Fisik Rumah dengan Kejadian Pneumonia pada Balita di Wilayah Kerja Puskesmas Jatibarang Kabupaten Brebes - Padmonobo, Heru; Setiani, Onny; Joko, Tri (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Pneumonia is the leading killer of children under the age of five years (Toddlers) in the world. In theworld, from 9 million deaths of more than 2 million children under five die every year due Toddler pneumonia orequal to 4 Toddler dies every minute of it. Jatibarang health center in the working area of 2009 there were 709cases of children suffering from pneumonia and increased to 747 in 2010. On the other hand a healthy housecoverage is only 36.40%.Methode : The purpose of this study was to determine the relationship between physical environmental factorswith the incidence of pneumonia at children under five years on PHC Jatibarang Brebes.This was an observational study with case control study design. The subjects were divided into two groups: case and control groups with 74 subjects in each group. Variables examined in this study were physical enviroment factors in housing with pneumonia on children under five years. Data was collected by interview, observation and measurement. Analysis of data using univariate analysis, bivariate with Chi-square and multivariate with logistic regression.Result : The result of bivariate analysis indicated that there was a correlation between the incidence ofpneumonia in children under five years with type of wall, type of floors, natural lighting, residential density, areaventilation, insulation kitchen, humidity room and toddler room temperature. With Odds Ratio (OR) in order:3.034 (p = 0.003); 2.635: 2.202: 2.234: 2.218: 2.517: 2.872 and 3.390. The results of logistic regression test showed that there was a significant association between the incidence of pneumonia in infants with room temperature, type of walls, spacious rooms with ventilation and humidity in sequence OR 4.380; 2.753; 2.734, and 2.671.Conclusion : The conclusion of this research indicated that the type of wall, type of floors, natural lighting,residential density, area ventilation, insulation kitchen, humidity room and toddler room temperature a riskfactor for pneumonia among children under fiveKeywords: Physical Environment of house, pneumonia, children under five years